Rationale: Photosynthesis of Vascular Plants in Dim Light - Wang, Xiaolin; Wang, Yong; Ling, Aifeng; Guo, Zhen; Asim, Muhammad; Song, Fupeng; Wang, Qing; Sun, Yanguo; Khan, Rayyan; Yan, Huifeng; Shi, Yi (Frontiers in Plant Science, 2020)
Light dominates the earth’s climate and ecosystems via photosynthesis, and fine changes of that might cause extensive material and energy alternation. Dim light (typically less than 5 μmol photons m–2 s–1) occurs widely in terrestrial ecosystems, while the frequency, duration, and extent of that are increasing because of climate change and urbanization. Dim light is important for the microorganism in the photosynthetic process, but omitted or unconsidered in the vascular plant, because the photosynthesis in the high-light adapted vascular leaves was almost impossible. In this review, we propose limitations of photosynthesis in vascular plant leaves, then elucidate the possibility and evidence of photosynthesis in terms of energy demand, stomatal opening, photosynthetic induction, and photosynthesis-related physiological processes in dim light. This article highlights the potential and noteworthy influence of dim light on photosynthesis in vascular plant leaves, and the research gap of dim light in model application and carbon accounting.